Mr. Keynes and the neo-Schumpeterians: Contributions to the analysis of the determinants of innovation from a post-Keynesian perspective - Jo\~ao P. Romero (EconomiA, 2014)
The purpose of this paper is to discuss the importance of knowledge, both tacit and codified, in the formation of the state of long-term expectations that drive firms' decisions to search for innovation and to investment in R&D. The paper takes the post-Keynesian theory as reference, associating it with the neo-Schumpeterian analysis of innovation dynamics. First, it is argued that knowledge plays a crucial role in building agents' confidence, emphasizing that radical innovations are more dependent on the accumulation of codified knowledge, given the higher degree of uncertainty associated with this type of innovation, while incremental innovations are more dependent on tacit knowledge about the current market conditions and technological trajectory. Second, it is argued that the accumulation of knowledge and the constant introduction of innovations foster the creation of a convention to innovate, which facilitates the decision to pursue innovations by influencing long-term expectations. – – O objetivo desse artigo é discutir a importância do conhecimento, tanto tácito como codificado, para a formaç\~ao do estado de expectativas de longo prazo que orienta as decis\~oes das firmas quanto à busca de inovaç\~oes e ao investimento em P&D. O artigo toma a teoria Pós-Keynesiana como referência, associando-a à análise Neo-Schumpeteriana da inovaç\~ao. Primeiro, argumenta-se que o conhecimento desempenha um papel crucial na elevaç\~ao da confiança dos agentes, enfatizando que as abordagens Pós-Keynesiana e Neo-Schumpeteriana s\~ao complementares, uma vez que a primeira coloca maior ênfase no conhecimento tácito e a segunda coloca maior ênfase no conhecimento codificado. Segundo, argumenta-se que que a acumulaç\~ao de conhecimento e a constante introduç\~ao de inovaç\~oes contribuem para a criaç\~ao de uma convenç\~ao a inovar, a qual facilita a decis\~ao de busca de inovaç\~oes ao influenciar as expectativas de longo prazo.
Keywords: O32; E12; G11; 330; Innovation; Post-Keynesian theory; Neo-Schumpeterian theory; Technology